Increasing Students’ English Reading Comprehension Through Novel Text in Extensive Reading Class: English - Rifari Baron; Sufi Alawiyah (Journal of English Development, 2023)
Abstract  The purpose of this study was to determine the effectiveness of fiction  novel texts in improving students' English reading comprehension skills. This study used an experimental approach using a one-group pre-test and post-test design. The sample of this research was postgraduate students of the English Education Study Program, at Indraprastha University, Jakarta. There were 50 students involved in the research process. The process of collecting data using tests and observations. The data that has been obtained will be tested for its normality level using the Kolmogorov-Smirnov test and the data homogeneity test using the Analysis of Variance test with a confidence level = 0.05. Data that has been declared normal and homogeneous is then processed using a two-sample paired t-test for the average. The results showed that t stat < t-table (-28.767 < 2.0638). This means that novel texts have a positive influence on students' English reading comprehension and that for literal, inferential and critical understanding. This finding has implications for lecturers that the learning resources provided by the problems faced can have a good impact on student learning outcomes.